2016
DOI: 10.1111/aec.12450
|View full text |Cite
|
Sign up to set email alerts
|

Right here, right now: Populations of Actinotus helianthi differ in their early performance traits and interactions

Abstract: Populations across the geographical distribution of a species are shaped by different local environments to produce distinctive patterns of variation in plant traits. Among-population variation is, therefore, important for understanding potential shifts in distributions under changing environments, but is often not included in studies. In particular, critical data on the suitability of local environments for plant traits expressed at different life stages are lacking. To address this we performed two experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…; Emery et al . ). Failure to germinate can have profound consequences for ecosystem processes affecting community composition, species abundance and population dynamics (Walck et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Emery et al . ). Failure to germinate can have profound consequences for ecosystem processes affecting community composition, species abundance and population dynamics (Walck et al .…”
Section: Introductionmentioning
confidence: 97%
“…This fascicle appeared in November 1805, just two months after Labillardière had published Actinotus helianthi in his Novae Hollandiae plantarum specimen. Plants of Actinotus helianthi in Australia can produce flowers in as little as eight months from seed (Worrall et al 2004), but seed viability is reported to be low after 153 days (Emery et al 2017). Naturaliste with Baudin expedition collections left Sydney on 18 November 1802, reaching France in June 1803, so that it is just conceivable that some seeds survived the voyage, the resultant plant(s) flowering in Paris -to be drawn, but then die out completely soon afterwards.…”
Section: Cultivated In France?mentioning
confidence: 99%
“…Actinotus helianthi, a closely related fire ephemeral, and have also demonstrated a complex dynamic of germination cues (Emery et al 2011). We aimed to understand the dormancy and germination cues of the Pink Flannel Flower to give insights both for improving its use in cultivation and its ecology in the wild.…”
Section: Introductionmentioning
confidence: 99%